The Contribution of the Labor Union in Improving the Welfare of Workers at PT. Sari Makmur Tunggal Mandiri - Desen, Kana; Maswandi, Maswandi; Isnaini, Isnaini (Journal of Public Representative and Society Provision, 2025)
Trade unions have an important role in improving workers' welfare through legal protection mechanisms, negotiations, and advocacy for workers' rights. This study aims to analyze the legal regulation of trade unions in Indonesia, its existence in improving the welfare of workers, and the role of the United Indonesia Sunggal Labor Union in PT. Sari Makmur Tunggal Mandiri. This research uses a qualitative method with a descriptive approach, which involves interviews, observations, and document analysis. The results of the study show that labor unions are legally recognized based on Law Number 21 of 2000 and Law Number 13 of 2003 concerning Manpower, but in their implementation there are still obstacles, such as a lack of understanding of workers' rights to union and pressure from companies. The existence of trade unions has had a positive impact on improving workers' welfare, especially in terms of wages, health benefits, and the reduction of unilateral termination of employment (PHK). However, workers' participation in trade union activities is still low due to fear of negative impacts on their careers. This study concludes that labor unions have a significant contribution in fighting for the welfare of workers in PT. Sari Makmur Tunggal Mandiri, but its effectiveness is still influenced by regulatory factors, government support, and active involvement of workers. Therefore, it is necessary to increase socialization regarding workers' rights, strengthen supervision by the government, and the company's commitment to building fairer industrial relations.